Mapping the biopolitics of borders: Bodies, places, deterritorializations - Αθανασίου Αθηνά; Τσιμουρής Γιώργος (The Greek Review of Social Research, 2013)
In the current context of crisis, precarity emerges as a condition for constituting certain subjects as “foreign bodies”. The subjectivating norms of migration and gender, in their inextricable relationship with economic and class status, are deployed as techniques of border demarcation and biopolitical regulation. Specific gendered and ethnicized/racialized subjects, through their subsumption under essentialist typologies of superfluous bodies, are turned into abjected exceptions of the political order: ideal “others”, ideal victims. In this context, the discursive regime of national, proprietary, white and heteronormative masculinity is established as a norm that determines the human and the political. The gendered and the national positioning, in their performative co-implication, crucially affect the ways in which the apparatuses of displacing and emplacing unfamiliar others produce and demarcate the space of the political community. How does the articulation of gender and migration work to produce different enactments and embodiments of the ‘glocal’? How are nationalisms de-territorialized and re-territorialized through significations and practices of gender, sexuality, and migration? If power and resistance are intertwined, how do abjected subjects, rendered superfluous and alien, return to the political arena, and how do they unsettle the violence through which they have been produced as abject?